The art of business communication : how to use pictures, charts and graphs to make your message stick - Shaw, Graham (Pearson, 2015)
Whether it's in emails, documents, presentations, meetings or tweets, we're all being bombarded by millions of words every day. So, how do you make your message stand out and stick amongst all this chatter? The answer is simple - just get visual! With a straightforward doodle or a quick illustration you'll revolutionise how your message impacts your audience. And The Art of Business Communication will show you how to do it. Can't draw? No Picasso? No problem! You'll be amazed at how easy it is to add a simple yet powerful visual dimension to any message or business communication so that all your ideas, presentations, documents and meetings are brought to life and make a meaningful and memorable impact. Everything becomes easier to say, problems are explained and solved in a flash and the complex quickly becomes clear. So, to make your point and make it matter - make it visual.